Ethical and legal points of view in parenteral nutrition - Guidelines on Parenteral Nutrition, Chapter 12. - Rothaermel, S.; Bischoff, S. C.; Bockenheimer-Lucius, G.; Frewer, A.; Wehkamp, K. H.; Zuercher, G. (GMS German Medical Science, 2009)
Adequate nutrition is a part of medical treatment and is influenced by ethical and legal considerations. Patients, who cannot be sufficiently fed via the gastrointestinal tract, have the fundamental right to receive PN (parenteral nutrition) even so patients who are unable to give their consent. General objectives in nutrition support are to supply adequate nutrition with regards to the prevention of malnutrition and its consequences (increased morbidity and mortality), and thereby promoting improved outcome and/or quality of life for the patient considering always the patient's needs and wishes. The requests of the patient to renounce PN should be respected where a signed living will is helpful. During the course of a terminal illness the nutrition has to be adapted individually according to the needs and wishes of a patient in the corresponding phase. Capability of consent should be checked in each individual case and for each measure on an individual basis. Consent should only be accepted if the patient is capable of recognizing the nature, meaning and importance of the intervention as well as the consequences of relinquishment of such an intervention, and is capable to make a self-determined decision. If the patient is not capable of consenting, the patient's living will is the most important document when determining their assumed will and legally binding. Otherwise a guardian appointed by the patient, or the representative appointed by the court (if the patient has made no provisions) can make the decision.
CRIS-Team Scopus Importer:2025-03-13